Review Paper: ‘Discourses on the Place of Mothers Rights where They Are Subject to Domestic Violence within Child Protection Work in England’ - Littlechild, Brian (Sustainability, 2021)
This article examines the place of gendered relationships between parents with regard to child protection work in England, and the effects of this on mothers who are abused by their male partners. These areas are discussed within an emotionally, socially, and politically charged set of issues concerning to what extent the State should intervene, why, and how between parents and their children in terms of parental rights and child protection. In this way, the article examines fault lines in the Western world’s ideology of the family, and concepts and realities of parental, mothers’ and children’s rights. In examining dominant and competing discourses on parental rights in child protection work, the case is made for the need to disaggregate concepts and approaches away from parental rights per se, to viewing the possibility of needing to see fathers and mothers needs and rights as at times being in conflict. This becomes particularly problematic in relation to mothers’ rights to their own protection from abuse, and how this relates to professional interventions when both the mother and the children are being abused. It considers the need to acknowledge and foreground taking account of how the mother and child(ren) are experiencing the abuse, not how society and professionals might like to view the situation by way of an idealized view of families through a particular ideological lens.